Total body skin examination increases squamous cell carcinoma detection: a retrospective cohort study. (18th June 2019) - Ali, Z.; Todd, P. M.
Summary: Squamous cell carcinomas (SCCs) have the potential for local tissue destruction and metastasis. The risk of complications increases if the lesion is not diagnosed and excised in a timely manner. Total body skin examination (TBSE) has been reported to increase melanoma detection; the objective of this study was to determine if it also increases SCC detection. Analysis of 469 SCCs diagnosed at a UK tertiary centre showed that 6.8% of these were detected incidentally and not from the index lesion that prompted referral. These incidentally detected SCCs tended to represent early disease, and therefore carried lower risk of complications. Our findings suggest that full skin checks may increase the number of SCCs detected, and at an earlier stage of disease. Therefore, we encourage the use of TBSE in all dermatology outpatient appointments, and make suggestions as to how to incorporate it into the limited time available in dermatology clinics.